Comparison between urban and rural mortality in patients with acute myocardial infarction: a nationwide longitudinal cohort study in South Korea. Issue 4 (8th April 2020) - Kim, Hye Sim; Kang, Dae Ryong; Kim, Inah; Lee, Kyungsuk; Jo, Hoon; Koh, Sang Baek
Abstract : Objectives: This study investigated the risk associated with interhospital transfer of patients with acute myocardial infarction (AMI) and clinical outcomes according to the location of the patient' residence. Design: A nationwide longitudinal cohort. Setting: National Health Insurance Service database of South Korea. Participants: This study included 69 899 patients with AMI who visited an emergency centre from 2013 to 2015, as per the Korea National Health Insurance Service database. Primary outcome measure: The clinical outcome of a patient with AMI was defined as mortality within 7 days, 30 days and 1 year. Results: Clinical outcomes were analysed and compared with respect to the location of the patient's residence and occurrence of interhospital transfer. We concluded that the HR of mortality within 7 days was 1.49 times higher (95% CI 1.18 to 1.87) in rural patients than in urban patients not subjected to interhospital transfer and 1.90 times higher (95% CI 1.13 to 3.19) in transferred rural patients than in non-transferred urban patients. Conclusions: To reduce health inequality in rural areas, a healthcare policy considering regional characteristics, rather than a central government-led, catch-all approach to healthcare policy, must be formulated. Additionally, a local medical emergency delivery system, based on allocation of roles between different medical facilities in the region, must be established.